Financial Development, Financial Structure and Income Inequality in China. (19th August 2016) - Liu, Guanchun; Liu, Yuanyuan; Zhang, Chengsi
Abstract: Using panel data of 23 provinces during the period 1996–2012, this paper investigates the impacts of financial development and structure on income inequality in different administrative districts (urban, rural and overall) in China. The results produced by the dynamic generalised method of moments estimator provide some evidence for a linear and inverse 'U‐shape' relationship between financial development and income inequality, and increasing the relative importance of financial markets to banks helps to reduce income inequality. Furthermore, the results of panel threshold regressions show that the benefits of financial development only occur if the stock market activity has reached a threshold level and disappear if the stock market capitalisation has reached a certain scale. Meanwhile, the impact of the financial structure weakens as the financial development expands and the proportion of financial markets increases. We also find that the impacts of financial development and structure on rural income inequality are stronger than those on urban income inequality.